Instructional Media and Methods in the Implementation of a Curriculum Reform: A Case of Entrepreneurship Education in Uganda - Luyima, Jimmy; Ndawula, Stephen; Kasirye, Richard (Asian Journal of Social Sciences & Humanities, 2014)
This study focuses on the role of Instructional media and Methods in curriculum reform implementation of Entrepreneurship Education in Uganda. It examines how instructional media and methods have affected the achievement of the overall vision of introducing Entrepreneurship Education in secondary schools, as curricula innovation geared at equipping students at secondary schools with Entrepreneurship skills for self employment. The study took a qualitative approach with 30 respondents purposively sampled. It was concluded that majority of the teachers of Entrepreneurship were ill prepared and did not have relevant instructional materials. At the same time, teachers never had adequate time to conduct field lessons. It was therefore recommended that, Teacher Training Institutions adopt Entrepreneurship Education a core subject so as to produce fully qualified teachers; National Curriculum Development Centre (NCDC) to produce enough instructional materials and avail them on market and orient teachers on the use of appropriate methods.
Keywords: Instructional Materials, Instructional methods, Curriculum, Entrepreneurship Education, National Curriculum Development Centre (NCDC)